The impact of music in consumer behavior: Applied to television commercials of fast moving consumer goods - Ferreira, Vera Bruna Gonçalves (2022)
Our lives are filled with music, it follows our days, stays in our minds, brings memories, and has the capacity of changing our feelings and emotions. Music has the power of being an extraordinary tool, if used wisely and operating its full capacities. Hence, the emotions and actions that music origins in consumers are a crucial input in business. Better understand in how the publicity world can benefit the most from the use of music, can help marketeers to make more effective and efficient decisions. Therefore, this dissertation aims to study the impact that background music of television commercials has in consumer’s behaviour. In this study, commercials from fast moving consumer goods in the beverages sector, were manipulated and analysed in order to further investigate the topic. The research combines and complements previous studies by taking in consideration a variety range of emotions and analysing different features that involve the music elements in a commercial. Concepts like brand recall, congruency of advertising elements, purchase intentions, moods and emotions are addressed and tested. The results show that the emotions transmitted through music have, as expected, a significant influence on the perception of the listener towards the brand and product, and consequently the impact on purchase intention of consumers.